The use of bacterial DNA from saliva for the detection of GAS pharyngitis. Issue 1 (1st January 2020) - Hashavya, Saar; Pines, Naama; Gayego, Ayelet; Schechter, Avi; Gross, Itai; Moses, Alon
ABSTRACT: Background: Acute tonsillitis is a very common medical condition. Despite different methods of detection, all tests are based on GAS sampling using a throat swab. However, obtaining the swab can elicit vomiting and is often accompanied by fear and apprehension in children. The aim of this study was to find a non-invasive method for the detection of GAS pharyngitis. Methods: A classic throat swab was obtained for culture, and a saliva sample was taken from 100 subjects recruited from Meuhedet Health Care Organization clinic. Real time PCR was performed to detect GAS dnaseB specific gene in the saliva samples. Results: 56% of the throat cultures and 48% of the PCR samples were positive for GAS. The overall sensitivity and specificity of the saliva PCR method was 79% and 91% respectively; NPV and PPV were 77% and 92% respectively. When excluding patients who presented on the first day of fever, sensitivity and specificity increased to 90% and 100% respectively. No other anamnestic or clinical findings increased the yield of the test. Conclusion: Saliva-based PCR amplification of GAS DNA method is effective in detection of GAS pharyngitis. Further studies are needed to achieve detection rates to replace the traditional throat swab-based approach.